Changes in the Maternal Risk Factors of Congenital Heart Disease in Chinese Population: A Meta-analysis - Jiang, Di; Bai, Chenxiao; Wang, Liwen; Chen, Ou (Cardiology and Cardiovascular Medicine, 2019)
Objective: To explore whether there were any changes in the maternal risk factors of congenital heart disease (CHD) in Chinese population between the ten years before 2008 (1999-2008) and the ten years after 2008 (2009-2018). Methods: Databases including PubMed, Web of Science, Wanfang Data, China National Knowledge Infrastructure, Chinese Scientific and Technological Journal Database and China Biology Medicine disc were retrieved and reference lists of related articles were checked to collect relevant studies. Meta-analysis was conducted to calculate the pooled OR and 95%CI. Subgroup analyses, meta regression, sensitivity analysis and publication bias were further performed. Results: A total of 44 studies were included in the meta-analysis. In the ten years before 2008, 6 risk factors including colds, infections, and medication use during pregnancy, exposure to chemical toxic substances during pregnancy, negative life events during pregnancy, and abnormal childbearing history were identified. While in the ten years after 2008, 12 factors were identified. The 6 new factors were periconceptional folic acid supplementation, vitamin supplementation, living near major traffic roads, living or working near factories, living in newly renovated rooms, and passive smoking during pregnancy. Conclusion: The maternal risk factors of CHD in Chinese population has changed greatly between the ten years before 2008 and the ten years after 2008. People’s concerns on living environments, lifestyles, and pregnancy care have been greatly increased in recent years. Notably, environmental pollution has become an important issue endangering maternal and fetal health in the ten years after 2008 in China.